A Preliminary Analysis of the Importance of Distance, Angle, and Insight When Soccer Referees Make Penalty Decisions - Bjørn Tore Johansen; Martin Kjeøen Erikstad (Frontiers Media S.A., 2021)
Soccer referees move freely on the pitch to place themselves in the best location for making decisions. While Football Association UK (FA) highlights that a referee should never be more than 20 m away from the playing situation, previous studies have been inconsistent in indicating appropriate distance to a situation for increasing the likelihood of a correct decision. Further, appropriate angle and insight are also likely to influence the correctness of referees' decisions. The aim of this study was to provide an initial investigation of elite referees' positioning in the field (distance, angle, and insight) when making correct and erroneous decisions in potential penalty situations. An expert panel (EP) consisting of two active referees with relevant academic background analyzed referees positioning when making correct or erroneous decisions regarding penalties. The EP were asked to qualitatively analyze referees positioning in selected video clips by using recommended technical refereeing criteria and practical guidelines (i.e., the referee's distance from, angle to, and insight into the penalty situations). Of the 42 situations evaluated, the results revealed that the EP termed the referees positioning as good in terms of angle and insight in 25 and 21 situations, respectively. The angle was average in seven situations and poor in 10 situations, and the insight were average in 10 situations and poor in 11 situations. The match referee was <10 meters away in 12 situations, 10-20 m away in 22 situations, and >20 meters away in eight situations. Results revealed that referees' positioning that resulted in the highest rate of correct decisions were when the distance were under 10 meters (83% correct decisions), good angle (88%), and good insight (86%). In contrast, referees were poorly positioned in terms of angle and/or insight in nine of the 15 erroneous decisions made. Although the present study was a preliminary qualitative investigation containing a limited number of potential penalty situations, the findings indicated that soccer referees are more likely to produce a correct decision in potential penalty situations when the distance to the situation is under 10 meters, when the insight to the situation is good and the angle to the incident is good. In contrast, the match referees generally had a poor starting position to assess the penalty situations where they landed on a wrong decision. While previous studies have been somewhat inconsistent in indicating optimal referee positioning in soccer, the present study highlights the potential value of a more qualitative approach to understand referees' positioning and subsequent decision-making accuracy.